PROFIL BERPIKIR SISWA PESERTA OLIMPIADE MATEMATIKA DALAM MENYELESAIKAN MASALAH ALJABAR - Latifah, Izza Wardatul; Susanto, S; Sugiarti, Titik; Fatahillah, Arif; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2018)
Abstract. This study aims to describe the profile of generalization thinking, simplifying problems, and analytic thinking of mathematical olympiad students in solving algebraic problems. The research subjects were 4 mathematical olympiad students at SMPN 2 Jember. Tests and interviews are used to collect data. Based on the analysis of the data, the results of the study show that the mathematical olympiad students can solve the given problems using non-procedural methods. They prefer to use a more effective and efficient way. In process of simplifying problems, the students can represent problems into mathematical models using algebraic forms. In making mathematical models, the students use variables as a form of example. In this study, there are still students who use symbols as variables that showing those students are still at the stage of iconic thinking according to J.Bruner's learning theory. In the analytical thinking process students are able to solve problems using the methods they obtain from the results of their analysis of the given problems. In the generalization thinking process students can find and apply existing rules or patterns to solve the given problem, even though there are still students who have not received the material. They are able to solve problems using reasonal and logical thinking. Keywords: Mathematical Olympiad, Generalization, Simplifying Problems, Analityc Thinking.